Importance and significance of information sharing in terrorism field - Abaas, Thamer; Shibghatullah, Abdul Samad; Yusof, R. (Publications International, 2014)
Years after the 11th Sept 2001 have led in researchers to re-structure intelligence and counter terrorism in technology information to overcome problems and issues related to terrorism. This work provides an updated research of Information and Communication technology (ICT) related to re-structuring of intelligence and counter-terrorism. For this purpose, the objectives of this work is to conduct a survey on the conceptual view of the researchers who developed tools for electronic information sharing employed in intelligence and counterterrorism and summary of their works in this emerging field. The work discusses the different visions and views of information sharing, critical infrastructure, tools and key resources discussed by the researchers. It also shows some of the experiences in countries considered as international reference on the subject, including some information-sharing issues. In addition, the work carries out a review of current tools, software applications and modelling techniques around anti-terrorism in accordance with their functionality in information sharing tools. The work emphasises on identifying the various counter terrorism related works that have direct relevance to information transportation researches and advocating security informatics studies that are closely integrated with transportation research and information technologies related to the recommendations of the 9/11 commission report in 2004. The importance of this study is that it gives a unified view of the existing approaches of electronic information sharing in order to help developing tools used in intelligence and counter terrorism for future coordination and collaboration in national security applications.